2006
DOI: 10.3732/ajb.93.4.517
|View full text |Cite
|
Sign up to set email alerts
|

Variability in leaf optical properties of Mesoamerican trees and the potential for species classification

Abstract: Leaf traits and physiological performance govern the amount of light reflected from leaves at visible and infrared wavebands. Information on leaf optical properties of tropical trees is scarce. Here, we examine leaf reflectance of Mesoamerican trees for three applications: (1) to compare the magnitude of within- and between-species variability in leaf reflectance, (2) to determine the potential for species identification based on leaf reflectance, and (3) to test the strength of relationships between leaf trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
100
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(114 citation statements)
references
References 54 publications
8
100
0
6
Order By: Relevance
“…A unique biochemistry and spectral signal is considered neither in the biological definition of a species, nor in the ecological classification of plant assemblages [6]. Further, species-specific biochemistry and spectral signal show a large spatio-temporal variation due to site conditions and other external influences [4]. This hampers a direct inversion of the relationship towards a quantification of the floristic composition and makes the direct mapping or classification of vegetation with remote-sensing approaches very challenging.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A unique biochemistry and spectral signal is considered neither in the biological definition of a species, nor in the ecological classification of plant assemblages [6]. Further, species-specific biochemistry and spectral signal show a large spatio-temporal variation due to site conditions and other external influences [4]. This hampers a direct inversion of the relationship towards a quantification of the floristic composition and makes the direct mapping or classification of vegetation with remote-sensing approaches very challenging.…”
Section: Introductionmentioning
confidence: 99%
“…In particular at global and regional scales, where ground-based mapping is inefficient, remote sensing may be a practical alternative approach for vegetation mapping. Environmental conditions, such as climate, also affect the biophysical and biochemical properties of species and hence influence their spectral signal [4,7]. Environmental conditions, especially temperature and precipitation, are further major determinants of species distribution at macroscales [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating spectral variation within species, Castro-Esau et al (2006) found sufficient difference in the optical properties of species sampled across multiple sites that accurate automated classification was impossible.…”
Section: Introductionmentioning
confidence: 99%
“…Resasco et al [23] were able to map an invasive shrub in understorey vegetation based on comparisons of seasonal differences in vegetation indices. In several recent studies, phenological differences in leaf traits [24] and canopy characteristics [25] allowed discrimination of vegetation at the species level based on leaf spectral signatures. In the context of bush encroachment in Namibia, known differences in leaf phenology of the encroacher species could facilitate distinguishing between the two prevailing Acacia species based on multi-temporal remote sensing imagery.…”
Section: Introductionmentioning
confidence: 99%